Análisis del rendimiento y utilidad del proceso de aserrío de trocería de pino - Zavala Zavala, David; Hernández Cortés, Raúl (Instituto de Ecología, A.C., 2016)
In this study a sample size of 87 logs was determined to achieve a 95% confidence, based on the variation of the lumber recovery of a presample of 37 logs. From the logs sampled, 43% were classified as high quality, 26% as medium and 31% as poor quality. Regarding the diameter, 89.65% were within a range of 30 to 55 cm. A lumber recovery factor of 51% was determined and a proportion of slabs and end trims of 27% and 22% of sawdust. The quality and diameter of the logs did not seem to have any influence on lumber recovery, but a relationship was found between log quality and lumber quality, logs of 1st and 2nd class produced 31.70% and 19.44% of quality lumber, logs of 3rd class generated 33.60% of 3rd grade lumber, logs of 4th and 5th grade produced 34.79% and 29.18% of 4th and 5th lumber grade respectively. A log price of $432.00 per m3 and a processing cost of $510.95 per mbf were determined. Comparing the costs of these two concepts with the price of the lumber, a revenue of $968.18 per mbf was determined.